2017
DOI: 10.5943/cream/7/4/5
|View full text |Cite
|
Sign up to set email alerts
|

Species richness and composition of arbuscular mycorrhizal fungi occurring on eucalypt trees (Eucalyptus camaldulensis Dehnh.) in rainy and dry season

Abstract: River red gum (Eucalyptus camaldulensis Dehnh.), the most commonly planted eucalypt species globally, has several advantages and is widely used for many purposes, which makes the tree important. Mycorrhizal establishment in eucalyptus has been known for many years, and the benefits of this symbiosis have been commercially explored. The main goal of this research was to assess the diversity and distribution of arbuscular mycorrhizal fungi (AMF) on eucalyptus planted in agricultural fields in the rainy and dry s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 35 publications
2
3
0
1
Order By: Relevance
“…Previously, Nongkling and Kayang (2017) had indicated that the OM, soil moisture, and nutrient content were the factors responsible for AMF species richness in the soils. Similar with Khaekhum et al (2017), found that the number of AM fungal spores in the rhizosphere of eucalyptus was higher soil moisture content (rainy season) and lower in low soil moisture content (dry season). Furthermore, a high level of P had a negative effect on AM fungal distribution (Rubio et al 2003;Alguacil et al 2010).…”
Section: Discussionsupporting
confidence: 78%
“…Previously, Nongkling and Kayang (2017) had indicated that the OM, soil moisture, and nutrient content were the factors responsible for AMF species richness in the soils. Similar with Khaekhum et al (2017), found that the number of AM fungal spores in the rhizosphere of eucalyptus was higher soil moisture content (rainy season) and lower in low soil moisture content (dry season). Furthermore, a high level of P had a negative effect on AM fungal distribution (Rubio et al 2003;Alguacil et al 2010).…”
Section: Discussionsupporting
confidence: 78%
“…According to Mangan et al (2004), seasonality affects the occurrence of AMF as the species produce their spores at different times of the year, and these become physiologically active in seasons which are more conducive to their development. Reductions in the number of spores in the dry season were also observed by Khaekhum et al (2017) and Ramos-Zapata et al (2011) in eucalyptus stands and coastal dunes, respectively.…”
Section: Speciessupporting
confidence: 65%
“…Plant growth-promoting fungi (PGPF) are ubiquitous fungi symbiotically associated with plants such as endophytic fungi (EPF) and arbuscular mycorrhizal fungi (AMF) [5][6][7]. These fungi can promote the growth of their host plants and also protect the plants from diseases [4,[8][9][10].…”
Section: Introductionmentioning
confidence: 99%